PENCEGAHAN KEKERASAN TERHADAP ANAK DALAM RUANG LINGKUP KEJAHATAN KDRT DI DESA AMBOLOLI KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Fitriah Faisal; Herman Herman; Handrawan Handrawan; Isnayanti Isnayanti; Idris Saputra (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
This Community Service Activity is entitled "Prevention of Violence Against Children within the Scope of Domestic Violence Crimes in Ambololi Village, Konda District, South Konawe Regency". The aim of this community service activity is to increase knowledge of law and prevent violence against children within the household (domestic violence). The stages of activities that will be carried out are as follows: (a) preparation stage includes: survey; stabilization and determination of locations and targets; preparation of training materials/materials, which include: presentation materials, powerpoint slides, (b) the implementation stage includes: (1) Explanation of material regarding the concept of violence against children in the household, the subject of protection and how to report cases of child violence in the context of domestic violence based on statutory provisions as a form of education to village communities. (2) This legal counseling activity is carried out by a community service team from the university involving students. The methods used during the process of community service activities include: (a) the lecture method is chosen to provide direct explanations about the extension material, (b) the Question and answer method which allows the community to gain as much knowledge as possible about the extension material. Based on the results of community service activities carried out in Mitra village, it can be concluded that this activity was attended by 30 people consisting of the community and village officials. Legal education can increase the knowledge and understanding of the Ambololi Village community regarding the prevention of violence against children within the household scope. So, that it has an impact on the formation of legal awareness in the community to jointly realize the spirit of Law no. 23 of 2002 concerning child protection and Law no. 23 of 2004 concerning the elimination of domestic violence.